Characterization and isolation of an 18-crown-6 complex of potassium hydroxide prepared by milling: application to mechanochemical organic synthesis. (7th March 2023) - Vugrin, Leonarda; Halasz, Ivan; Geneste, Hervé
Abstract : Solid-state supramolecular complexation of potassium cations enables the reactivity of KOH in mechanochemical organic reactions. Abstract : The enhanced mechanochemical reactivity of potassium hydroxide (KOH) in the presence of 18-crown-6 ether is supported by potassium complexation under milling and has been demonstrated in the Henry reaction and SN Ar hydroxylation: in both cases, the desired product is formed within 10 minutes, but requires the presence of the crown ether.